ТрF1 - a new potential antigen for serological diagnostics of latent forms of syphilis - A. V. Runina; K. V. Rog; M. M. Vasilev (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The current diagnostics of sexually transmitted diseases is focused on the search for new diagnostically important antigens, especially antigens of T. pallidum that causes syphilis. This article describes the recovery of the recombinant protein TpF1, a cytoplasmic bacterioferritin of T. pallidum, and a study of its immunogenicity in blood serum samples taken from patients with different forms of syphilis and from healthy volunteers. The authors performed a heterologous expression of the TpF1 protein in E. coli cells and purified the recovered TpF1 by means of metal-chelate affinity chromatography. The recombinant TpF1 was further used as an antigen for the determination of specific IgG for this protein in serum samples taken from patients suffering from primary, secondary and early/late latent forms of syphilis. According to the study results, anti-TpF1 antibodies are present at all stages of syphilis yet the level of such antibodies revealed in the groups of patients suffering from secondary, early and late latent forms of syphilis was statistically significantly different from the level of antibodies in the group of healthy volunteers. The greatest difference was observed in the groups of latent syphilis. These data characterize the TpF1 protein as a promising antigen for the diagnostics of syphilis, and TpF1 can also be considered as a potential antigen for the differential diagnostics of latent forms of syphilis.